THE ROLE OF SOCIAL MEDIA IN THE DISSEMINATION OF ISLAMIC DA‘WAH AMONG YOUTH - Dhimas Agus Prasetyo; Fathorrahman Fathorrahman (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
This study aims to analyze the effectiveness of Islamic da‘wah through social media in reaching youth, with a focus on three major platforms: YouTube, Instagram, and TikTok. The background of this research arises from the phenomenon of increasing social media usage among adolescents, which not only serves as a means of entertainment but also becomes a medium for the dissemination of religious values. The method employed is descriptive qualitative, with data collection techniques including in-depth interviews, participatory observation, and documentation of digital da‘wah content. The data were then analyzed using data reduction, data presentation, and drawing conclusions, with validity tested through source and method triangulation. The results indicate that social media plays a significant role in expanding the reach of da‘wah to youth, particularly through short, creative content, visually appealing materials, and a communicative style of language. Nevertheless, digital da‘wah also faces several challenges, such as low digital literacy, social media algorithms that prioritize entertainment, and the limitations of content duration in conveying profound religious messages. Recommended strategies include optimizing content upload times, collaborating with Islamic influencers, and enhancing digital literacy and social media ethics among youth. Thus, this study confirms that social media holds great potential as a medium for contemporary da‘wah, provided it is managed with appropriate, innovative strategies aligned with the needs of the youth audience.